Rights of inmates mother in relation to child custody / Rosliah Abdul Ramlan and Lydiana Mansor. - Abdul Ramlan, Rosliah; Mansor, Lydiana (2006)
Rule 13(1) of the Rules of Prison 2000 ('the rule 13(1)') allows only child below three years to reside with the mother in prison and after the stipulated age, the child must be separated from the mother. While Article 9(1) of the Conventions on the Rights of the Children (CRC) provides inter alia, that child and parent(s) cannot be separated against their will except by a competent authority, subject to judicial review. Thus rule 13 seems to be in contrast with the provision in CRC. The next issue is as a consequence of imprisonment of the wife, the husband may claim to have a sole custody of the children contending that the wife has lost her right of custody to the child for being an inmate. It is found that although the rule 13(1) allow the separation of child at the age of three or four years, the age which is considered as still young, but, since it is within the scope of Article 9(1) of the CRC, whereby, the prison authority is a competent authority to make such rule, therefore, rule 13(1) cannot be said as inconsistent with the provision in CRC. Additionally, experts advised that it is for the best interest of the child to be separated from the mother even at the young age and it is also universally accepted that prison is not suitable for the mental and psychological development of a child. On the other hand, a mother does not lose her rights of custody to her children due to her imprisonment.